Evaluación del enraizamiento a partir de la aplicación de un biorregulador de crecimiento en yemas de banano musa sp con la variedad william - Quichimbo Ochoa, Juan Alberto (2014)
With the method of the technique to take starting root from the application of a bioestimulante of yolks in banana tree seed was looked for to diminish the investment costs for the stump purchase it was the center of the present investigation, for which thought about the following objectives: 1.- o settle down the best propagation method is for division of seeds agamic in banana tree of the variety Williams among the treatments and 2.- To determine which the best substrate to obtain the best percentage of plants spread for the seedtime or definitive transplant.The investigation was carried out in the experimental farm Santa Inés of the Facultad of Agricultural Sciences of the Technical University of Machala. The area of the test according to the registrations of INAMHI possesses a half temperature of 24º C, a half annual precipitation of 630 mm, hours light average of five hours depending on the time, a relative humidity of 90%, the floors are of texture arcillo - oozy, and with a neuter pH of 7. According to the area of natural life of Holdridge the region corresponding to a Humid Forest. Tropical (bh. T). The uses Stumps of banana tree of hybrid Willams, planting substrate, glass boxes and tools. The treatments were T1. 1 stump - 3 yolks + kelpak; T2 ½ stump with 1 yolks + Kelpak; T3. ½ stump + 2 yolks + Kelpak 10 cc; T4 Son of water + 3 yolks + Kelpak and Witness (stump with 3 yolks).The variables in study for the present research work were the to take the following root: Percentage to the 30, 45 and 60 days, I Number of yolks stimulated by stump, Height of yolks to the 30 and 45 days, Number of leaves to the 30 and 45 days, Percentage of functional roots to the 60 days, Long of the roots to the 60 days and Weight of the roots to the 60 days. The methodology included, Selection of the material: 1 healthy and vigorous banana tree stump was used; type "green onion" and that they have from one to three "yolks" each one and for treatment; to the selected stumps they were removed the earth remains with abundant water, and with a knife the roots are eliminated, parts of the stump that are affected by damages caused by plagues or microorganisms and the air portion, only leaving a portion that allows to hold it with the hand. Disinfection: got a ready solution of water and chlorine to reason of 5 ml for liter of water, in which submerged the stumps during 10 minutes for their disinfection. Seedtime: the clean and disinfected previous stumps to the Seedtime dove in a solution of Kelpak during 10 minutes for then to be sowed in the previously prepared glass boxes with their substrate and to the 30 days you began to evaluate the variables. The experimental design employee was, Totally at random with five treatments and two repetitions:The novísima technology of developing the production of yolks to the stumps of banana tree of the variety Willams which a sustrato is managed enriched with humus, humus macerated with hidróxido of potassium more Bioestimulante Kelpak of Basf. The stimulation for the formation of yolks starting from "a stumps with three yolks + the bioestimulante 10 ml (T2) and T3. "Half stump with two yolks + Kelpak" produced the best results in the analysis from the relative variables to the height of the yolks, and I develop of the system radicular in weight and volume to the 60 days. The traditional witness was overcome by the experimental different treatments; without existing outstanding differences among using the whole stump or divided in two parts.